Kinerja Pengembangan Potensi Perikanan Dalam Peningkatan Pendapatan Asli Daerah Di Provinsi Maluku Utara - Djabir Salim; Prince Charles Heston Runtunuwu*; Nahu Daud (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
The development of marine and fisheries in North Maluku Province is very important and strategic because it has very large and reliable fishery resource potential. The development of community fisheries through commercial fisheries is carried out to increase fishery capacity with improvements that must be made to be able to encourage regional economic growth in North Maluku Province. This study aims to analyze the potential role of fisheries in increasing local revenue (PAD) in North Maluku Province. The method used in this research is Location Quotient (LQ) Analysis and Regression Analysis. The results of the study show that the value (LQ) proves the potential income of the fisheries sector has a positive relationship to regional original income. The fisheries and marine sector as a leading sector based on regional income indicators should require strong efforts from the government to be willing to provide services for the development of fisheries and maritime affairs in North Maluku Province.